3D Finite Element Analysis of Geogrid-Reinforced Pavement Performance under Heavy Vehicle Loading in a Curved and Graded Highway Section over Weak Subgrade: A Case Study of Bishaltar, Nepal - Shrestha, Prashanna; Tiwari, Aanchal; Tiwari, Ram Chandra; Jha, Prabhat Kumar (International Journal on Engineering Technology, 2026)
The Bishaltar section of Prithvi Highway in Dhading District, Nepal, is a critically distressed pavement segment characterized by combined horizontal curvature (R=40m) and longitudinal gradient (G=4.56%), along with high super elevation (e=6.8%) and a very weak subgrade (california bearing ratio, CBR=2.83%, modulus, E=2.83×10⁴ kPa). Despite being designed using IRC and Department of Roads (DoR) guidelines for an 80kN standard axle load and 30 million standard axle (MSA) through IITPAVE software, the pavement has exhibited persistent surface distresses, early rutting, and premature fatigue cracking, often rendering it unrepairable due to recurring structural deficiencies. A detailed 3D finite element analysis using PLAXIS 3D with Mohr-Coulomb material modeling was conducted, incorporating 27 loading phases to simulate the complex stress path induced by a 12-wheeled 33 Ton gross weight truck under curved and upgraded conditions. Results show that geogrid placement at the subgrade-base interface (SB) is most effective for rutting control, achieving service life ratio (SLR) values of 1.576 (vertical compressive strain, εzz) and 1.588 (Principal compressive strain, ε1). The combined SB and base-asphalt (BA) configuration provides maximum transverse strain reduction (54.7%, SLR=2.207), whereas BA alone is detrimental, increasing subgrade strain. Geogrid stiffness influence is minimal, with EA=300-600 kN/m identified as performance optimal. The study highlights the limitations of conventional design approaches and underscores the necessity of reinforcement-based design for critical curved and graded highway sections.